Accuracy of cotton-planting forecasts assessed in the San Joaquin Valley - Douglas Munier; Peter Goodell; Joyce Strand (California Agriculture, 2004)
In the first evaluation of its kind, we found that the UC Cooperative Extension (UCCE) 5-day degree-day forecast for cotton-planting conditions performed well in Bakersfield and Fresno when compared with the actual, observed temperatures from 1998 to 2002. In most cases, the forecast provided timely advice during the critical cotton-planting period. On average, only 7% of the forecasts failed to predict unfavorable conditions. Better-than-expected weather occurred 9% of the time when unfavorable conditions were forecast. On average during the 22 planting days of March (beginning March 10, the first allowable planting date in the San Joaquin Valley), 2.5 days (11%) were incorrectly forecast to have better-than-unfavorable planting conditions. In April, the cottonplanting forecasts were more reliable, with only 1 day out of 30 (3%), on average, that may have required replanting because of unpredicted, unfavorable conditions.